2018
DOI: 10.3389/fphys.2018.01179
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Produces Persistent Increases in Plasma Corticosterone, Reductions in Brain and Cardiac Nitric Oxide Production, and Delayed Alterations in Endothelial Function in Young Prehypertensive Rats

Abstract: This study was designed to investigate whether oxidative stress, nitric oxide (NO) deficiency and/or endothelial dysfunction (ED) are present in young borderline hypertensive rats (BHR) and whether these pathologies can be causally involved in the initiation of blood pressure (BP) increases. Additionally, we tested the hypothesis that crowding stress, experienced during the peripubertal period, may produce persistent or delayed disorders in corticosterone release, NO synthesis, oxidative status and/or endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…These findings, together with the significant positive correlation with behavioral tests, show the ability of CMI to modulate hyperactivity of the HPA axis, an effect that can play a role in its antidepressant properties. The alterations in the HPA axis are caused especially when there is exposure to acute stress (Browne et al, 2014), but some authors demonstrated the alteration in the corticosterone levels caused by long-term stress (Dallman et al, 2004;Bernatova et al, 2018). In addition, HPA axis activation can produce damaging physiological effects and exert a profound impact on brain function (McEwen, 2000;Tsigos and Chrousos, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, together with the significant positive correlation with behavioral tests, show the ability of CMI to modulate hyperactivity of the HPA axis, an effect that can play a role in its antidepressant properties. The alterations in the HPA axis are caused especially when there is exposure to acute stress (Browne et al, 2014), but some authors demonstrated the alteration in the corticosterone levels caused by long-term stress (Dallman et al, 2004;Bernatova et al, 2018). In addition, HPA axis activation can produce damaging physiological effects and exert a profound impact on brain function (McEwen, 2000;Tsigos and Chrousos, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in the HPA axis are caused especially when there is exposure to acute stress (Browne et al, 2014 ), but some authors demonstrated the alteration in the corticosterone levels caused by long-term stress (Dallman et al, 2004 ; Bernatova et al, 2018 ). In addition, HPA axis activation can produce damaging physiological effects and exert a profound impact on brain function (McEwen, 2000 ; Tsigos and Chrousos, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Elevated plasma cortisol levels are common in patients with anxiety [40]. In CMS models, the persistency of elevated plasma corticosterone levels has been demonstrated after stress withdrawal [41,42]. Elevated corticosterone in CS + ST, which was similar to the CS condition, can be justified by persistency of the effect of the two stressors, CMS and swimming training, on corticosterone, which continued for a relatively long time (eight weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic disorders affecting the endothelial function, such as those seen in smokers [10], in patients with early atherosclerosis [33], or in patients with diabetes [12], alter these mechanisms and hamper the production of NO, resulting in an impairment of vasodilation response [3436].…”
Section: Discussionmentioning
confidence: 99%